Comportamento informacional dos docentes dos PPGCIS da região nordeste - Forte, Jofrany Dayana Pessoa (2014)
It analyzes the informational demands of the PPGCIs' professors from the Northeast Region concerned with both teaching and research practice. The Sense-Making approach, by the American – Brenda Dervin, was applied in order to base the research, so as to understand the meaning the individual assign to information at the moment in which one realizes a cognitive gap, while proceeding to a determined task, configurating the situation-gap-use triad. It refers to a descriptive research on a quantitative qualitative basis. A mixed questionnaire was employed as the data gathering‟s tool. Bardin‟s categorization technique was used to analyze the researched users‟responses. Twenty-two Professors took part in the research. The achieved results displayed that they usually search for information in Information Units, such as libraries, archives and documentation centers. Furthermore, to respond to informational needs, the greatest part of the researched individuals use the internet as information source. Concerning information channnels, they make use of books, journal articles, monographs, dissertations, theses, research reports, special collections.The major part of the researched perceive that such channels improve teaching practice because they keep themselves up to date with the following aspects: issues that are being discussed in classroom, the discovery of new methodological approaches, the updating of the existing knowledge as well as new experiences. As to the search process and to the information use, the greatest aim is to update knowledge on the researcheds‟ area, and to seek to information in order to apply on researches. The most recent problem which has led them to information search and use has been the demand for informational material that could have been applied as the support to carry on researches in process. The Professors state that whenever they are engaged in such a process, they – as a whole – become satisfied. In this context, normally, the feeling that prevails the mentioned search process is, somehow, some questioning; in other words, the need to find out something new about a certain issue, a gap, a cognitive empty. Barrier time is one of the informational obstacles that mostly hampers the information search process and use, as well as the information excess to which everyone is subject nowadays. The most used strategy to overcome such a barrier is the selection by means of the trustfulness criterion. Therefore, the knowledge about the informational behavior has demonstrated itself, considering the Professors‟ speech, as an alternative to know how they are doing to handle the informational bulk and to retrieve relevant information to use in their teaching practice.